The children's Bible in 365 stories - Mary Batchelor; Haysom, John (Icknield Way, Tring, Herts, England ; Belleville, Mich., USA : Lion Pub., 1985)
An illustrated collection of 365 stories retold from the Bible, from Genesis to Revelation.
"A Lion book."
Includes index.
Keywords: Holy Bible Texts and Translations (3fUhU hJQLeGJ GdcJGH GdebOSs; Bible stories, English; Bible stories. -- Bible